PENGARUH TINGKAT PENDIDIKAN, INVESTASI, DAN TINGKAT UPAH TERHADAP ANGKATAN KERJA YANG AKTIF BEKERJA DI INDONESIA - Vivi Violita Firda; Syamsul Amar (Jurnal Ecogen, 2018)
This study aims to find out and analyze the influence of (1) Education Level, (2) Investment, and (3) Wage Levels on the workforce that is actively working in Indonesia by using the panel regression equation model and using the Fixed Effect Model (FEM) approach. The estimation results show that (1) Education Level has a positive and significant effect on the workforce that is actively working in Indonesia, (2) Investment has a positive and not significant effect on the workforce that is actively working in Indonesia, (3) Wage Levels have a positive and significant effect on workforce that is actively working in Indonesia.This type of research is descriptive and associative. Data type is secondary data. This study uses panel data, which uses 32 provinces in Indonesia using the Fixed Effect Model (FEM) approach.The results of this study indicate that: (1) Education Level has a positive and significant effect on the Active Work Force in Indonesia (2) Investment has a positive effect and has no significant effect on the Active Work Force in Indonesia. (3) Wage Levels have a positive and significant effect on the Active Work Force in Indonesia. Keywords: Labor Force, Education Level, Investment, and Wage Level